Zebrafish as a Model Organism to Study Nanomaterial Toxicity - Jaison Jeevanandam; Yen San Chan; Michael Kobina Danquah (Ital Publication, 2019)
Recent developments in nanotechnology has increased the market value of nanoproducts in various industries. This has increased concerns associated with potential toxicity of nanoproducts to humans and the environments. Even though, green and biosynthesized nanoparticles are considered to be less toxic than chemically synthesized nanoparticles, they still possess some level of toxicity. Conventional toxicity assessments via human cells, live animals such as rat, frog or rabbit have several drawbacks including ethical issue and challenges involving the maintenance and development of cell cultures. Zebrafish (Danio rerio) is a transparent vertebrate fish that can reproduce rapidly. Its larvae develop in 5 days up to 3-5 cm long. It also possesses about 69% similar genetic profile, molecular mechanism, cell development and organ physiology as humans. Hence, it has the potential to be utilized as an alternative to humans or live animal models for initial drug screening and toxicity tests. European Union, USFDA and ICH have approved the use of zebrafish for toxicological evaluation of pharmaceutical products including nanomedicines. The article presents for the potential of zebrafish in preclinical evaluation of the toxicity of nanomaterials. It also discusses other potential applications, including medical imaging and environmental toxicity.